2008
DOI: 10.1007/s00253-008-1439-9
|View full text |Cite
|
Sign up to set email alerts
|

A chemoenzymatic approach to the synthesis of enantiomerically pure (S)-3-hydroxy-γ-butyrolactone

Abstract: Optically pure (S)-3-hydroxy-gamma-butyrolactone, an important chiral building block in the pharmaceutical industry, was synthesized from L: -malic acid by combining a selective hydrogenation and a lipase-catalyzed hydrolysis. Lipase from Candida rugosa was found to be the most efficient enzyme for the hydrolysis of (S)-beta-benzoyloxy-gamma-butyrolactone. The use of organic solvent-aqueous two-phase system was employed to extract benzoic acid generated from enzymatic hydrolysis of the substrate. Tert-butyl me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…However, we found only two examples of selective L-malic acid hydrogenation to ( S ) −3-HBL and ( S ) −1,2,4-butanetriol using mono-and bimetallic catalysts [28,29] . In addition, optically pure ( S ) −3-HBL can be produced by chemoenzymatic method, i.e., via selective hydrogenation of malic acid over zinc borohydride catalyst followed by hydrolysis with enzymes [30] or via direct biosynthesis from glucose [31] .…”
Section: Introductionmentioning
confidence: 99%
“…However, we found only two examples of selective L-malic acid hydrogenation to ( S ) −3-HBL and ( S ) −1,2,4-butanetriol using mono-and bimetallic catalysts [28,29] . In addition, optically pure ( S ) −3-HBL can be produced by chemoenzymatic method, i.e., via selective hydrogenation of malic acid over zinc borohydride catalyst followed by hydrolysis with enzymes [30] or via direct biosynthesis from glucose [31] .…”
Section: Introductionmentioning
confidence: 99%
“…A continuous chemical synthesis process employing high pressure hydrogenation of L-malic acid over a ruthenium-based catalyst in a fixed-bed reactor has been developed for the commercial synthesis of (S)-3HBL at a capacity of 120 tonnes per year 8,9 ; however, this process employs hazardous processing conditions and expensive catalyst and purification processes. The various other chemical and chemoenzymatic routes developed for 3HBL synthesis 3 also suffer from similar disadvantages including the use of hazardous materials and processing conditions 10,11 , expensive starting materials, reagents and catalysts [11][12][13][14][15] , and poor yield and difficult to separate by-products 10,12,13,16 , driving up the cost of the product. Biosynthesis is expected to alleviate many of these problems and offer an elegant solution towards economical production of this valuable chemical; however, this requires the design of a novel biosynthetic pathway 17,18 .…”
mentioning
confidence: 99%
“…); however, when the process is at a yield More than 40% is in operation, the enantiomeric purity of 24 is diminished. Lee et al [50] from the LG chemical company recently reported the synthesis of 24, which uses three synthesis steps (Scheme 24). The two initial steps of this synthesis were done directly.…”
Section: Scheme 23 Synthesis Of Compound 24 By Catalytic Reaction Wimentioning
confidence: 99%